Acute Abdomen due to Primary Omental Torsion and Infarction. (6th November 2014) - Occhionorelli, S.; Zese, M.; Cappellari, L.; Stano, R.; Vasquez, G.
Abstract : Background . Torsion of greater omentum is a quite uncommon cause of acute abdomen. It can be primary or secondary but in both cases omentum twists upon itself and causes omental segmentary or diffuse necrosis. Symptoms are unspecific and preoperative diagnosis is difficult. The widespread and increasing use of computer tomography (CT) in differential diagnosis of acute abdomen can be useful for making a specific diagnosis. Objectives . This work aims to describe primary omental torsion in order to help avoid misdiagnosis, especially with acute appendicitis, which is eventually based solely on a physical examination. Case Report . We present a case of primary omental torsion in a young man and discuss contemporary methods in diagnosis and management of the condition. Conclusions . When a right diagnosis has been posed, possible treatments for omental torsion and necrosis are two: conservative or surgical. Conservative treatment had been rarely carried out because of frequent and important sequelae just like abdominal abscesses. Nowadays, surgical treatment, laparoscopic or laparotomic, is preferred because it is a safe method in diagnosis and management of this condition.